Treatment of Pediatric Inflammatory Myofibroblastic Tumor: The Experience from China Children's Medical Center - Youhong Dong; Kashif Rafiq Zahid; Yidi Han; Pengchao Hu; Dongdong Zhang (MDPI AG, 2022)
Background: Inflammatory myofibroblastic tumor (IMT) is a rare mesenchymal tumor with intermediate malignancy that tends to affect children primarily. To date, no standardized therapies exist for the treatment of IMT. This study aimed to share experience from China Children's Medical Center for the explorative treatment of IMT. Methods: Patients with newly diagnosed IMT between January 2013 and December 2018 were included. Patients were grouped according to surgical margins and Intergroup Rhabdomyosarcoma Study Group (IRSG) staging. The clinical characteristic, therapeutic schedules, treatment response and clinical outcome were described. Results: Six patients were enrolled in this study, including two boys and four girls, with a median age of 57 months (range 10-148 months). Among them, five patients were anaplastic lymphoma kinase positive. Four patients achieved complete remission and two patients attained partial remission after treatment with this protocol. All patients were alive after a median follow-up of 4 years (range 3-7 years). The most common treatment-related adverse reaction was myelosuppression. Conclusion: In this study, we demonstrated that IMT has a good prognosis and the treatment selected according to risk stratification was effective and feasible.